Seroprevalance of Toxoplasma, Rubella, and Cytomegalovirus during Pregnancy - Amanullah Bhutto, Maria, Nahil Shams, Aqsa Noureen, Huma Ishtiaq, Kiran Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: Many infectious and congenital diseases caused by bacteria and viruses affect the health of both mother and fetus. Today, an epidemic with the common name TORCH affects women during pregnancy, especially during the first trimester. Method: The current study investigates the pathogens and routes of transmission and the percentage of antibodies in the blood against toxoplasma, rubella and cytomegalovirus. The first 20 weeks usually develop in pregnant women and can be fatal if the infection is passed on to the fetus. Although these infectious diseases cannot be adequately treated, several vaccines are being introduced into the pharmaceutical industry to treat pregnant women during pregnancy and prevent fetal death. Results: Data were collected from the Liaquat Jamshoro School of Medicine and Department of Public Health Pathology in affected women and summarized as follows. Transmission of cytomegalovirus and rubella is most common compared to toxoplasma. A CMIA test (chemiluminescent micro particle immunoassay) was performed to obtain highly accurate data on the responsible IgG and IgM antibodies in the blood of pregnant women. In this case, CMIA is considered very reliable. Conclusion: Throughout the study, it was observed that these viruses can cause fetal malformations or ultimately death if left untreated in pregnant women. It is said to spread knowledge about the treatment and struggle of disease. Keywords: CMV; CMIA; Rubella; TORCH; Toxoplasma;